Lesson Study-Based Collaborative Mathematics Learning Model in Higher Education - Orisa Capriyanti; Arista Khairunnisa; Dina Yulita; Tia Amelia (Newinera Publisher, 2026)
This study examines the implementation of a Lesson Study based collaborative mathematics learning model and its contribution to student learning outcomes, learning activities, and lecturers’ pedagogical development in higher education. The study employed a mixed methods approach with an embedded design, integrating quantitative data from pretest, posttest, and learning activity observations with qualitative data from classroom observations, lecturer reflections, peer lecturer feedback, and learning documentation. The research was conducted in the Islamic Economics Study Program at STIES Nahdlatul Ulama Bengkulu, involving 28 students enrolled in the Economic Mathematics course, one course lecturer, and peer lecturers participating in the Lesson Study team. The intervention was implemented through three Lesson Study cycles consisting of planning, implementation, and reflection. The quantitative findings show that students’ overall mathematics learning outcomes increased from a pretest mean score of 58.00 to a posttest mean score of 77.50, with improvements observed across conceptual understanding, formula application, problem solving, mathematical reasoning, and contextual connection with Islamic economics. The highest gain was found in students’ ability to connect mathematical concepts with Islamic economics contexts. Qualitative findings further revealed that Lesson Study supported more reflective, adaptive, and student centered teaching practices through collaborative planning, classroom observation, and post lesson reflection. These findings suggest that integrating Lesson Study with collaborative mathematics learning can provide a meaningful instructional model for non mathematics students in Islamic higher education, especially when mathematical concepts are connected to relevant disciplinary contexts.